Defining Agile and Planned Method Fragments for Situational Method Engineering - Pereira, Guilherme Vaz; Fontoura, Lisandra Manzoni (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
Situational Method Engineering (SME) aims to build a specific software development method/process according to a project situation from reusable building blocks called method fragments. This paper proposes a metamodel for definition of method fragments. The proposed metamodel was elaborated from the integration between the RUP and ISO/IEC 24744 metamodels. It allows the fragment definition according to practices recommended by agile and planned methodologies.